GROSS AND HISTOLOGICAL STUDY OF HUMAN LIVER MORPHOLOGY INCLUDING SINUSOIDAL ARCHITECTURE AND ITS SURGICAL IMPLICATIONS - Dr. V. Subhashini Rani; Mrs V. Vinila (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Did we mention that liver, which is the largest gland in the human body, displays wide variation in gross morphology and sinusoidal microarchitecture? Such variations may manifest as pathologies on imaging or may add added difficulty to hepatobiliary procedures. Such studies must encompass both morphology and histology for relevant clinical insight. Materials and Methods: Among 36 formalin-preserved livers selected for descriptive cadaveric study at the Department of Anatomy, Konaseema Institute of Medical Sciences, February 2024 to July 2025. The gross features, which included lobes, fissures, grooves, impressions, and accessory lobes, were observed and classified according to Netter. Histological sections were stained with H&E, reticulin, and Masson’s trichrome for the assessment of lobular organization, portal triads, and sinusoidal arrangement. Results: Out of 36 specimens, 19 (52.78%) had normal morphology, whereas 17 (47.22%) were considered to have a variation. The abnormalities observed included accessory fissures (22.22%), pons hepatis (11.11%), quadrate lobe anomalies (11.11%), accessory lobes (2.78%), and diaphragmatic grooves (11.11%). Riedel’s lobe and saddle-shaped left lobes were also seen. Histology revealed a consistent classical lobular structure with hepatocyte cords radiating from central veins, fenestrated sinusoidal endothelium, and well-defined portal triads. Conclusion: Almost 50% of livers exhibited possible morphological variants that could simulate disease or complicate surgical intervention. Thus, awareness of such variants along with sinusoidal architecture is indispensable for the interpretation of imaging and safe practice.